Advances in underground mining technology in the Federal Republic of Germany - Friedrich Benthaus (Canadian Institute of Mining, Metallurgy and Petroleum, 1984)
"The natural and man-made realities on either side of the Atlantic are different. Therefore, a large part of the other side' s knowledge and experience cannot be transferred easily. In the following, the author will attempt to describe some of those developments in the German hard coal industry which may be of particular interest to readers on this side of the Atlantic.The area of the Federal Republic is quite small, especially if compared with a country as large as Canada. On a territory the size of the maritime provinces of New Brunswick and Nova Scotia, Germany holds coal reserves roughly corresponding to the total Canadian reserves. More than 20 billion tons of hard coal down to a depth of 1500 m, and more than 30 billion ton s of brown coal of lignite are technically and economically extractable acording to current technology.However, not only are Germany's coal resources more concentrated; the country is also densely populated, and there are dense networks of railroads and highways All components of the so-called infra-structure are available everywhere, be it electricity, any machinery or personnel. Public opinion is likely in favour of an increased utilization of coal.The coal industry is well developed through a long evolution covering centuries. As a consequence, there is an effective and intensive cooperation of numerous bodies and institutions concerned with coal mining, from government agencies including the inspectorate to suppliers, trade union s, producing companies, to jointly operated management and research organizations. In the Federal Republic, hard coal is mined in deep mines only, and lignite in general, only from open-cast pits. There is a complete organizational and geographic separation of hard and brown coal in Germany. Because the Federal Republic holds only insignificant mineral oil and very little natural gas deposits, coal is essentially the only and consequently the most valuable source of energy."